A Comparative Study of Levelized Cost of Electricity Between Photovoltaic and Concentrated Solar Powered Power Plants in Malaysia - Faizal, Bin Baharum; Muhamad Hanif, Bin Hassan; Mohd Dzulkarnaen, Bin Sudirman; Mohd Nasrun, Bin Mohd Nawi; Siti Halipah, Binti Ibrahim (Penerbit Akademia Baru, 2018)
Renewable Energy (RE) is crucial in energy generation towards a more sustainable and low-carbon approach. One of the well-known sources of RE is the sun through solar energy harvesting. Equatorial region like Malaysia seems to be at the very best advantage for generating energy from solar since that it receives sufficient solar radiation for the purpose. Photovoltaic (PV) and concentrated Solar Power (CSP) technology are the current technology in harvesting solar energy to generate power. However, referring to the Malaysian context today it seems that solar PV is the only technology practiced as one of the RE technologies that are eligible for tariff payment. The purpose of this study is to investigate the future prospect on current solar technologies which are PV and CSP by determining Levelized Cost of Electricity (LCOE) and land usage comparison to determining the cost comparative between solar technologies for future sustainable energy generation. The result is very positive as CSP has the advantage to be the future sustainable energy generation in Malaysia although there are some setbacks at the moment. Collaboration between all parties such as researchers, industry players as well as support from the government will aligned CSP on the right direction upcoming years to come.